Synthesis and assessment of la0.8Sr0.2Sc yMn1-yO3-d as cathodes for solid-oxide fuel cells on scandium-stabilized zirconia electrolyte - Gu, H.; Zheng, Y.; Ran, R.; Shao, Zongping; Jin, W.; Xu, N.; Ahn, J. (Elsevier SA, 2008)
Perovskite-type La0.8Sr0.2ScyMn 1-yO3-d oxides (LSSMy, y=0.0-0.2) were synthesized and investigated as cathodes for solid-oxide fuel cells (SOFCs) containing a stabilized zirconia electrolyte. The introduction of Sc3+ into the B-site of La0.8Sr0.2MnO3-d (LSM) led to a decrease in the oxides' thermal expansion coefficients and electrical conductivities. Among the various LSSMy oxides tested, LSSM0.05 possessed the smallest area-specific cathodic polarization resistance, as a result of the suppressive effect of Sc3+ on surface SrO segregation and the optimization of the concentration of surface oxygen vacancies. At 850°C, it was only ~0.094Ocm2 after a current passage of 400mA cm-2 for 30 min, significantly lower than that of LSM (~0.25 O cm2). An anode-supported cell with a LSSM0.05 cathode demonstrated a peak power density of 1300mWcm-2 at 850°C. The corresponding value for the cell with LSM cathode was 450mWcm-2 under the same conditions. The LSSM0.05 oxide may potentially be a good cathode material for IT-SOFCs containing doped zirconia electrolytes. © 2008 Elsevier B.V. All rights reserved.